Strategic hedging by smaller powers: what can neoclassical realism add? - Smith, Nicholas Ross (2018)
Hedging has become the strategic strategy de jure, particularly for smaller powers1 that find themselves in increasingly volatile regional settings. Both in practice and in literature, hedging has become somewhat mythologized as an ideal foreign policy for smaller powers; a strategy which avoids the costs of either balancing or bandwagoning. This paper argues that while hedging can indeed be a smart strategy for smaller powers to engineer more optimal outcomes, it is not only not a costless strategy but also a strategy which can be extremely difficult to effectively undertake. To shed light on the inherent limitations of smaller powers engaging in a hedge, this paper borrows from neoclassical realism. Neoclassical realism is a useful starting point here because it assumes that ideal foreign policy-making is impossible. In addition, in the context of smaller power hedging in the contemporary international setting, neoclassical realism’s understanding of systemic stimuli (aided by the literature on regional security complexes) and the domestic impact of strategic culture and leader images enables it to be a good analytical tool for gauging the likely challenges of attempting to hedge. Two historical examples, one of an ostensibly successful hedge (Tito’s non- alignment during the Cold War) and one of an ostensibly unsuccessful hedge (Yakub Beg’s failure to hedge the British and Russian Empires), are used to demonstrate how successful hedging requires adept understanding of the structural environment as well as a keen use of statecraft.